Problems with the Islamic legal system regarding child marriages in Indonesia during the covid-19 pandemic period - Anthin Lathifah; Briliyan Ernawati; Anwar Masduki (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2022)
The high number of child marriages during the Covid-19 pandemic period poses problems related to the Islamic legal system in Indonesia. This study aims to describe the problems of the Islamic legal system regarding the phenomenon of child marriages during the pandemic period in Indonesia. This paper is the result of a qualitative research with a socio-legal analysis approach, that is based on Friedman Hayden's legal system theory. The results of the study show that there are three substantial problems with the Islamic legal system, namely: (1) the problem associated with the legal substance where the Marriage Law stipulates the age of a bride to increase from 16 to 19-year-old as contained in article 7 paragraph (1) of the Marriage Law number 16 of 2019, while at the same time it enables child marriages to be carried out through a marital dispensation request, it acknowledges marital vows (ithbat), and there is an absence of legal sanctions for violating the Marriage Law; (2) the problem related to the legal structure of child marriages that is rooted in the formation, enforcement, and development of child marriage law; and (3) the problem of legal culture in relation to the legal behavior of child marriage, unregistered marriages (sirri) for minors, and the lack of social arrangements to promote the culture of marriage at a mature age. Therefore, this paper offers a reconstruction of the Islamic legal system in terms of legal substance, legal structure, and legal culture to minimize child marriage practices in Indonesia.